Determinan Investasi Portofolio di Indonesia: Pendekatan Vector Error Correction Model dan Error Correction Model - Ishfy Dinda Syafilla; Rini Dwi Astuti (FEB Universitas Sultan Ageng Tirtayasa, 2023)
The imbalances between investment financing and domestic savings in terms of providing sufficient capital are an obstacle to implementing economic development in Indonesia. Therefore, the flow of foreign capital is indispensable, one of which is by portfolio investment in order to increase capital market liquidity and as a source of financing domestic development. This study aims to analyze the response and influence of gross domestic product variables, inflation, exchange rates, and interest rates on portfolio investment in Indonesia in the period 2012.Q1-2021.Q4. The analytical tool in this study uses two approaches, which are: Vector Error Correction Model (VECM) and Error Correction Model (ECM). The results of this study indicate that in the long run, portfolio investment responds positively to the shock of inflation, exchange rate, and interest rate variables. In the short term, inflation and exchange rate variables have a negative and significant influence on portfolio investment.